Saponins: A class of bioactive natural products with wide applications in human health - Silva, Regildo Márcio Gonçalves da [UNESP] (2024)
Saponins are an important class of glycosides that occur in different plant species and can be steroidal or terpenoid types. They possess an amphiphilic character, in which a part of the structure presents a lipophilic characteristic and another hydrophilic characteristic (sugars), reducing surface tension in contact with water and establishing their detergent and emulsifier actions that can cause alteration in permeability and/or stability of cell membranes. The objective of this chapter was to describe and present saponins as bioactive compounds capable of application in the maintenance of human health through the treatment of different diseases, such as inflammatory, tropical, and degenerative diseases. Data from in vivo and in vitro assays regarding saponin activities were reported in several scientific studies, and they correspond to the accumulated knowledge about this class of compounds. These data demonstrated that the action of saponins on diseases is mainly associated with the structure and function of these compounds. These characteristics give saponins their activity on different etiologic agents and the physiological alterations caused by the pathological conditions. Therefore, the evolution of knowledge applied to the studies of saponins in human health showed the need for the integration of the scientific aspects and redefinition of the research processes for the development of drugs and products aimed at the treatment of inflammatory, tropical, and degenerative diseases.